EFFECTS OF Ti ADDITION ON THE DIELECTRICAL PROPERTIES OF A NEW AUSTENITE ALLOY - Aziz K. Jahja; Nurdin Effendi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2008)
EFFECTS OF Ti ADDITION ON THE DIELECTRICAL PROPERTIES OF A NEW AUSTENITE ALLOY. Preparation of alloys has been carried out leading to a new type of austenite alloys designated A-1 with a composition of Fe 52.22 wt%, Ni 24.2 wt%, Cr 20.0 wt%, Si 1.0 wt%, Mn 2.0 wt%, C 0.08 wt% and Ti 0.5 wt%. The main difference compared to commercial alloys (e.g. A347) is that Ti is added as an alloying element, but no P and S. The frequency-dependent conductivity and dielectric response of this novel material have been investigated by RLC bridge impedance spectroscopy method. It was verified that the real dielectric constant κ' of these newA-1materials showawell defined dielectric behavior and shows a considerable improvement over the commercial A-347 alloywith similar composition. Both dielectric response and dielectric loss curves show frequency dispersive relaxation peaks, indicating different conduction process in the surface and in the bulk of the materials. Therefore the substitution of P and S with Ti resulting in a new austenite with different dielectric properties. These improved dielectric properties should make this new material a good candidate for use as electrical connector, but with a reduced corrosion, so the lifetime or duration of application could be extended.